Modelling Free-Living and Particle-Associated Bacterial Assemblages across the Deep and Hypoxic Lower St. Lawrence Estuary - Ting Ting Cui (American Society for Microbiology, 2020)
ABSTRACT The Estuary and Gulf of St. Lawrence (EGSL) in eastern Canada are among the largest and most productive coastal ecosystems in the world. Very little information on bacterial diversity exists, hampering our understanding of the relationships between bacterial community structure and biogeochemical function in the EGSL. During the productive spring period, we investigated free-living and particle-associated bacterial communities across the stratified waters of the Lower St. Lawrence Estuary, including the particle-rich surface and bottom boundary layers. Modelling of community structure based on 16S rRNA gene and transcript diversity identified bacterial assemblages specifically associated with four habitat types defined by water mass (upper water or lower water column) and size fraction (free living or particle associated). Assemblages from the upper waters represent sets of cooccurring bacterial populations that are widely distributed across Lower St. Lawrence Estuary surface waters and likely key contributors to organic matter degradation during the spring. In addition, we provide strong evidence that particles in deep hypoxic waters and the bottom boundary layer support a metabolically active bacterial community that is compositionally distinct from those of surface particles and the free-living communities. Among the distinctive features of the bacterial assemblage associated with lower-water particles was the presence of uncultivated lineages of Deltaproteobacteria, including marine myxobacteria. Overall, these results provide an important ecological framework for further investigations of the biogeochemical contributions of bacterial populations in this important coastal marine ecosystem. IMPORTANCE The Estuary and Gulf of St. Lawrence (EGSL) in eastern Canada is an appealing ecosystem for studying how microbial communities and metabolic processes are related to environmental change. Ocean and climate variability result in large spatiotemporal variations in environmental conditions and oceanographic processes. The EGSL is also exposed to a variety of additional human pressures that threaten its integrity and sustainable use, including shipping, aquiculture, coastal development, and oil exploration. To monitor and perhaps mitigate the impacts of these human activities on the EGSL, a comprehensive understanding of the biological communities is required. In this study, we provide the first comprehensive view of bacterial diversity in the EGSL and describe the distinct bacterial assemblages associated with different environmental habitats. This work therefore provides an important baseline ecological framework for bacterial communities in the EGSL useful for further studies on how these communities may respond to environmental change.